Modelos para determinação da média mensal da fração difusa diária a partir de dados de reanálise meteorológica - (:unkn) unknown (Universidade Federal do Pampa, 2020)
The present study presents an analysis on the Solar radiation, which aims to estimate the diffuse radiation through the monthly mean of the diary diffuse fraction, using ERA5 meteorological reanalysis data. The validation of the reanalysis data was obtained from the comparison between the analysis data and those measured by the automatic stations of the National Institute of Meteorology (EMA/INMET), using the global radiation variable of 36 locations. From the ERA5 reanalysis, empirical models were calibrated for the determination of the monthly mean of the diary diffuse fraction, in 6 specific sites, by means of polynomials that use two different parameters. The socalled Groups 1, 2 and 3, use as parameter the number of hours of sunshine, the clarity index of the atmosphere and the two previous parameters combined, respectively. Each group contains quadratic and cubic polynomials. For all estimates correlation coefficients and errors were calculated in order to test their reliability, using as reference the ERA5 reanalysis. In most of the locations the best performance, when estimating the monthly mean of the diary diffuse fraction, was obtained by Group 3 that uses the ratio between the effective number of hours of sun and the possible number of hours of sun and the index of clarity mutually in the estimates. Correlations greater than 0.97 were obtained for this Group, and there was no significant distinction between the efficiency of the quadratic and cubic models.
Keywords: Engenharia; Radiação atmosférica; Engineering; Atmospheric radiation; CNPQ::ENGENHARIAS